If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) + -3(2x + 3) = 3(x + -5) Reorder the terms: 4(-3 + 2x) + -3(2x + 3) = 3(x + -5) (-3 * 4 + 2x * 4) + -3(2x + 3) = 3(x + -5) (-12 + 8x) + -3(2x + 3) = 3(x + -5) Reorder the terms: -12 + 8x + -3(3 + 2x) = 3(x + -5) -12 + 8x + (3 * -3 + 2x * -3) = 3(x + -5) -12 + 8x + (-9 + -6x) = 3(x + -5) Reorder the terms: -12 + -9 + 8x + -6x = 3(x + -5) Combine like terms: -12 + -9 = -21 -21 + 8x + -6x = 3(x + -5) Combine like terms: 8x + -6x = 2x -21 + 2x = 3(x + -5) Reorder the terms: -21 + 2x = 3(-5 + x) -21 + 2x = (-5 * 3 + x * 3) -21 + 2x = (-15 + 3x) Solving -21 + 2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -21 + 2x + -3x = -15 + 3x + -3x Combine like terms: 2x + -3x = -1x -21 + -1x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -21 + -1x = -15 + 0 -21 + -1x = -15 Add '21' to each side of the equation. -21 + 21 + -1x = -15 + 21 Combine like terms: -21 + 21 = 0 0 + -1x = -15 + 21 -1x = -15 + 21 Combine like terms: -15 + 21 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| 3g+2=2g+6 | | 3(2y-4)=9-3(y-1) | | X^2=-40 | | 3g+2=3g+6 | | 0.6y+6=y | | y+3(8+2y)=70 | | 9h-20-3h=-8 | | 6p-18-2p=-2 | | x=17-4y | | 2t^2-3t-5=0 | | 3(2x-1)-5(3x+1)=2 | | 6y^2+9y= | | 3x^3-x^2+11x-20=0 | | .66q-.75=.91 | | 6.7x=9 | | 7x+-5=x+1 | | 8.4=8.4 | | 9x+5=x+5 | | 9x-4=5x+8 | | X^2+32x+175=0 | | -4d+6-d=21 | | 12x+4=7x-24 | | 20-14a-15=6a | | 2m+13=23 | | 3(p+2)-3=7-p | | 2x^2+x=5 | | 7p+11+2q=0 | | 2x^3-10x^2+8x=0 | | 5v+29v+20=0 | | 4x+32=11x-38 | | 13x^2+6x+7=0 | | 5v=-25 |